A peculiar tale of vomiting – rumination syndrome in three adult patients - Alam, Laima; Alam, Mafaza; Faraid, Varqa (Journal of the Pakistan Medical Association, 2022)
Rumination syndrome is a functional gastrointestinal disorder with effortless, non-projectile regurgitation seen mostly in paediatric population and seems to be an uncommon gastrointestinal disorder due to lack of awareness among physicians. Here we report three such cases in adult patients that were labeled “refractory vomiting”. No such case has been reported from Pakistan which makes this a unique case series. All of our patients were diagnosed within six to fifteen months of initial symptoms, hence a high index of suspicion is required for early diagnosis of Rumination Syndrome to avoid excessive and repeated investigations, causing emotional trauma and financial loss to the patients and their families. Keywords: Manometry, ROME-IV, Rumination syndrome, Vomiting.